HASTE miniTEM Example Images - Blamey, Ben; Sintorn, Ida-Maria (Uppsala University, 2020)
Series of images of a sample of kidney tissue captured from the miniTEM (a 25keV transmission electron microscope) at Vironova offices in Stockholm (2019-02-04), for purposes of testing software related to the HASTE project (http://haste.research.it.uu.se/).
The dataset consists of 759 8-bit greyscale PNG images.

Used in this publication (and others):
Resource- and Message Size-Aware Scheduling of Stream Processing at the Edge with application to Realtime MicroscopyBen Blamey, Ida-Maria Sintorn, Andreas Hellander, Salman Toorhttps://arxiv.org/abs/1912.09088
Also"Rapid development of cloud-native intelligent data pipelines for scientific data streams using the HASTE Toolkit, GigaScience, Volume 10, Issue 3, March 2021, giab018, https://doi.org/10.1093/gigascience/giab018
Keywords: Distributed computing and systems software not elsewhere classified; Image processing; Medical and Health Sciences; Medicin och hälsovetenskap